Effects of Short-Term Treatment with α-Lipoic Acid on Neuropathic Pain and Biomarkers of DNA Damage in Patients with Diabetes Mellitus - Juozas R. Lazutka; Kristina Daniūnaitė; Veronika Dedonytė; Aistė Popandopula; Karolina Žukaitė; Žydrūnė Visockienė; Laura Šiaulienė (MDPI AG, 2024)
Background/Objectives: Diabetes mellitus (DM) is a complex and heterogenous disease classified as a group of metabolic disorders characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both. It leads to various complications, some of which are macrovascular or microvascular complications, like diabetic polyneuropathy (DPN), having a profound impact on patients' quality of life. Oxidative stress (OS) is one of the significant mechanisms in the development and progression of DPN. Thus, targeting OS pathways by antioxidants, such as α-lipoic acid (ALA), could represent a promising therapeutic strategy for alleviating neuropathic symptoms. The aim of our study was to evaluate whether short-term (from 4 to 9 days) intravenous administration of ALA could cause any measurable improvement in subjects with DM. Methods: Sixteen subjects with DM (six type 1 and ten type 2) and sixteen nondiabetic subjects matched by sex and age were recruited to this study. Only subjects with DM received treatment with ALA (600 mg daily). Pain intensity and biomarkers of DNA damage including plasma concentration of 8-hydroxy-2'-deoxyguanosine (8-OHdG), frequency of micronucleated lymphocytes (MN), and frequency of sister-chromatid exchanges (SCEs), were measured before and after the treatment with ALA. Results: Pain intensity and 8-OHdG levels were significantly lower in DM subjects after the ALA treatment than before the treatment. However, no changes in the frequency of SCEs and MN were observed. Conclusions: Our results show some evidence that even a short-term intravenous treatment with ALA could be beneficial for diabetic subjects, reducing pain intensity and concentration of 8-OHdG in blood plasma.